Democratization and Attempts to Modernize the Political System in The Republic of Moldova (Economic and Political Thought, 2024)
Today, when democracies are retreating worldwide and authoritarian regimes are becoming more and more repressive, Moldova is emerging as a “bright spot” in Europe. Despite economic and political challenges(,} democracy continues to grow in the country. Russia is trying to use different types of leverage to punish Moldova for its pro‑European position. This article’s purpose is to evaluate Moldova’s political evolution after independence in the post‑Soviet period. Although the country has gone through completely different stages of governance since independence, the main factors that hindered the attempt to establish a democratic regime in Moldova were the country’s precarious position in the international system, weak state institutions, a lack of rule of law and a profound rupture with national identity, which was further exacerbated by (S} systemic corruption deeply rooted in the country was aggravating. Moscow actively used the Transnistria conflict for years to limit Moldova’s pro‑Western aspirations.
Keywords: Republic of Moldova, oligarchic political system, post‑soviet country, Transnistria, systemic corruption